Oregano essential oil (Origanum vulgare) to feed laying hens and its effects on animal health - MIGLIORINI,MARCOS J. (2019)
Abstract Abstract: This study evaluated the effect of oregano essential oil added to the feed of commercial laying hens. This research was focused on the analysis of biochemical changes linked to hepatic function, and protein and lipid metabolism. It was used 240 laying hens (59 weeks-old) distributed in a completely randomized design of six treatments (five repetitions with eight birds each). The experiments were constituted by a control treatment (CT) with the inclusion of zinc bacitracin and five treatments of oregano essential oil (OEO: 0, 50, 100, 150, and 200 mg.kg-1), respectively. After 28 days of feeding, an increase on serum levels of total proteins and globulins was observed on groups T150 and T200, as well as an increase on albumin levels on group CT. After 84 days of feeding, a significant reduction on total proteins and albumin was observed on group T200, as well as an increase in serum triglycerides. OEO at 200 mg.kg-1 increased globulin levels on day 28, which may be considered an effect in the inflammatory response, which increases serum immunoglobulins and proteins.